Policy Implementation of the Electronic Identity Card Recording on Saturday and Sunday Through the Innovation Program by Civil Registry Service Office of Palangka Raya City - Muhamad Yusuf (Department of Public Administration, 2023)
The importance of ownership of administrative documents for Indonesian citizens is something that all elements of society know. However, this information is very difficult to pass on to some citizens. Public services appear in various forms. The research aims to determine the application of public service innovations in the Department of Occupation and Civil Registration of the City of Palangka Raya. With the presence of public services through the innovation program carried out, it is expected to increase access to the KTP recording. This type of research uses literature study techniques. Because information relevant to the subject or problem being studied is collected by the researchers during the data collection process, this information can be obtained in research reports, journals, scientific papers, theses and dissertations, regulations, encyclopedias, and written sources that are well printed and in the form of electronic data by describing the forms of application of public service innovations of PERSAMI in the Department of Occupation and Civil Register of the City of Palangka Raya. The results of the research described the application of public service innovation in the form of PERSAMI, which showed positive results in the E-KTP recording on the Disdukcapil City of Palangka Raya.